Hepatic Expression of PEMT, but Not Dietary Choline Supplementation, Reverses the Protection against Atherosclerosis in Pemt−/−/Ldlr−/− Mice. Issue 10 (3rd October 2018) - Zia, Yumna; Al Rajabi, Ala; Mi, Si; Ju, Tingting; Leonard, Kelly-Ann; Nelson, Randal; Thiesen, Aducio; Willing, Benjamin P; Field, Catherine J; Curtis, Jonathan M; van der Veen, Jelske N; Jacobs, René L
Abstract: Background: Phosphatidylethanolamine N -methyltransferase (PEMT) converts phosphatidylethanolamine to phosphatidylcholine. Pemt −/− /low density lipoprotein receptor ( Ldlr ) −/− mice have significantly reduced plasma lipids and are protected against atherosclerosis. Recent studies have shown that choline can be metabolized by the gut flora into trimethylamine- N -oxide (TMAO), which is an emerging risk factor for atherosclerosis. Objective: The objective of this study was to determine whether ectopic hepatic PEMT expression or choline supplementation would promote atherosclerosis in Pemt −/− /Ldlr −/− mice. Methods: Male 8- to 10-wk-old Pemt +/+ /Ldlr −/− (SKO) and Pemt −/− /Ldlr −/− (DKO) mice were injected with an adeno-associated virus (AAV) expressing green fluorescent protein (GFP) or human PEMT and fed a Western diet (40% of calories from fat, 0.5% cholesterol) for 8 wk. In a separate experiment, 8- to 10-wk-old SKO and half of the DKO male mice were fed a Western diet with normal (3 g/kg) choline for 12 wk. The remaining DKO mice [choline-supplemented (CS) DKO] were fed a CS Western diet (10 g choline/kg). Plasma lipid concentrations, choline metabolites, and aortic atherosclerosis were measured. Results: Plasma cholesterol, plasma TMAO, and aortic atherosclerosis were reduced by 60%, 40%, and 80%, respectively, in DKO mice compared with SKO mice. AAV-PEMT administration increased plasma cholesterol and TMAO by 30% and 40%, respectively, in DKO mice compared with AAV-GFP–treated DKO mice. Furthermore, AAV-PEMT–injected DKO mice developed atherosclerotic lesions similar to SKO mice. In the second study, there was no difference in atherosclerosis or plasma cholesterol between DKO and CS-DKO mice. However, plasma TMAO concentrations were increased 2.5-fold in CS-DKO mice compared with DKO mice. Conclusions: Reintroducing hepatic PEMT reversed the atheroprotective phenotype of DKO mice. Choline supplementation did not increase atherosclerosis or plasma cholesterol in DKO mice. Our data suggest that plasma TMAO does not induce atherosclerosis when plasma cholesterol is low. Furthermore, this is the first report to our knowledge that suggests that de novo choline synthesis alters TMAO status.